2016
DOI: 10.1016/j.trf.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Peer passenger norms and pressure: Experimental effects on simulated driving among teenage males

Abstract: Objective Serious crashes are more likely when teenage drivers have teenage passengers. One likely source of this increased risk is social influences on driving performance. This driving simulator study experimentally tested the effects of peer influence (i.e., risk-accepting compared to risk-averse peer norms reinforced by pressure) on the driving risk behavior (i.e., risky driving behavior and inattention to hazards) of male teenagers. It was hypothesized that peer presence would result in greater driving ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 53 publications
5
23
0
Order By: Relevance
“…The combined sample had a mean of 1.91% change toward the confederate’s attitude and a standard deviation of 24.65%. Consistent with behavioral reports using these data ( Bingham et al , 2016 ), these behavioral results indicate a bias toward conformity to the confederate’s attitude, but the large amount of variance confirms its value for understanding individual differences in susceptibility to social influence for risky behaviors.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The combined sample had a mean of 1.91% change toward the confederate’s attitude and a standard deviation of 24.65%. Consistent with behavioral reports using these data ( Bingham et al , 2016 ), these behavioral results indicate a bias toward conformity to the confederate’s attitude, but the large amount of variance confirms its value for understanding individual differences in susceptibility to social influence for risky behaviors.…”
Section: Resultssupporting
confidence: 82%
“…This research was part of a five-study investigation of the effects of peer influence on teen driving ( Falk et al , 2014 ; Simons-Morton et al , 2014 ; Cascio et al , 2015b ; Bingham et al , 2016 ; Schmälzle et al , 2017 ). A previous study in this research program found an association between neural activation during exclusion and risk taking ( Falk et al , 2014 ), and prior reports on the driving simulator data reported here noted substantial individual variability in susceptibility to influence ( Bingham et al , 2016 ). In this analysis, we extend these results by examining a measure of global functional connectivity during exclusion vs inclusion and investigate its predictive relationship with individual differences in conformity ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, greater risk taking in the presence of peers is consistent with a group polarization effect of peer influence, such that when drivers think peer passengers expect them to drive aggressively, they are more likely to do so. However, when peers are not expected to hold these preferences, adolescent drivers are no more likely to drive in a risky manner ( Bingham et al, 2016 , Simons-Morton et al, 2014 ).…”
Section: Cognitive Control Vs Experience-based Cognitive Developmentmentioning
confidence: 99%
“…In the first area, researchers in the past have investigated various factors that are contributing to crashes involved with teen drivers, such as speeding [4,5], distracted driving [6,7], driver age and gender [8,9], risky behavior [10], impaired driving [11], night-time driving [12], and peer passengers [13,14]. In the second field, many researchers have developed prediction models on crash severity, which can be generally divided into two groups: parametric models and nonparametric (or machine learning) methods.…”
Section: Literature Reviewmentioning
confidence: 99%